Gender patterns in Vietnam's child mortality - Thong Le Pham; Peter Kooreman; Ruud H. Koning; Doede Wiersma (Institute for the Study of Labor (IZA), 2011)
We analyze child mortality in Vietnam focusing on gender aspects. Contrary to several other countries in the region, mortality rates for boys are substantially larger than for girls. A large rural-urban mortality difference exists, but much more so for boys than for girls. A higher education level of the mother reduces mortality risk, but the effect is stronger for girls than for boys.
urn:nbn:de:101:1-201106013914
Keywords: C13; C31; C35; C41; I12; 330; child mortality; gender differences; hazard rate; frailty model